Semiotic Analysis of the Advertisement “iPhone 15 Face ID” Using Peirce’s Theory - Fairuz Khalisha; R. Myrna Nur Sakinah; Andang Saehu (JELITA, 2025)
This research aimed at analyzing how Apple’s Face ID technology is represented in the advertisement “iPhone 15 Face ID” using Charles Sanders Peirce’s semiotic theory. This study highlights how Peirce’s semiotic elements—icon, index, and symbol—are employed to emphasize privacy, personalization, and innovation in the iPhone 15 advertisement. Utilizing a constructivist methodology and qualitative research, this study focused on the visual, linguistic, and contextual components of the advertising and used the coding method for data analysis. The analysis focuses on how the advertisement leverages these elements to position Face ID not just as a security feature, but as an integral part of a personalized and private user experience. The findings contribute to a deeper understanding of how semiotics are employed in contemporary advertising to shape consumer perceptions of technology. The advertisement’s narrative shows that the others failing to access the device, highlighting its advanced security features. The rightful owner’s success reinforces the technology’s precision and the importance of privacy in modern society.